Does Greek Conservation Policy Effectively Protect the Cultural Landscapes? A Critical Examination of Policy’s Efficiency in Traditional Greek Settlements - Katapidi, Ioanna (European Spatial Research and Policy, 2015)
The paper discusses the role of Greek conservation policies in protecting the cultural landscape with focus on traditional Greek settlements. Drawing on secondary data but also on empirical evidence the paper examines the contribution of above policies to the protection of cultural landscapes.The first part focuses on the legislative framework, providing a critical examination regarding the way that cultural landscape is approached. The second part discusses the effects of this policy on a group of traditional settlements in central Greece, presenting the achievements and drawbacks of conservation policy as viewed by experts and residents in the area.